Association of blood glucose change with postoperative delirium after coronary artery bypass grafting in patients with diabetes mellitus: a study of the MIMIC-IV database - Wang, Fujun; Mei, Xue (Frontiers in Endocrinology, 2024)
Aim:This study focused on the patients with diabetes mellitus (DM) undergoing coronary artery bypass grafting (CABG) and explored the associations of different blood glucose related indexes and blood glucose change trajectory with postoperative delirium (POD).Methods:Data of DM patients undergoing CABG were extracted from the Medical Information Mart for Intensive Care (MIMIC)-IV database in this retrospective cohort study. The blood glucose related indexes included baseline blood glucose, mean blood glucose (MBG), mean absolute glucose (MAG), mean amplitude of glycemic excursions (MAGE), glycemic lability index (GLI), and largest amplitude of glycemic excursions (LAGE). The MBG trajectory was classified using the latent growth mixture modeling (LGMM) method. Univariate and multivariate logistic regression analyses were utilized screen covariates and explore the associations of blood glucose related indexes and MBG trajectory with POD. These relationships were also assessed in subgroups of age, gender, race, estimated glomerular filtration rate (eGFR), international normalized ratio (INR), sepsis, mechanical ventilation use and vasopressors use. Additionally, potential interaction effect between blood glucose and hepatorenal function on POD was investigated. The evaluation indexes were odds ratios (ORs), relative excess risk due to interaction (RERI), attributable proportion of BG and POD in DM patients undergoing CABG 3 interaction (AP) and 95% confidence intervals (CIs).Results:Among eligible 1,951 patients, 180 had POD. After adjusting for covariates, higher levels of MBG (OR=3.703), MAG (OR=1.754) and GLI (OR=1.458) were associated with higher odds of POD. The positive associations of MBG, MAG and GLI with POD were observed in patients aged <65 years old, male, White, eGFR <60, INR <1.5, sepsis, mechanism ventilation and vasopressors use (all P<0.05). Patients with MBG trajectory of class 3 (OR=3.465) and class 4 (OR=3.864) seemed to have higher odds of POD respectively, comparing to those who with MBG trajectory of class 1. Moreover, MAG (RERI=0.71 and AP=0.71) and GLI (RERI=0.78 and AP=0.69) both had a potential synergistic effect with INR on POD.Focusing on levels of MBG, MAG, GLI and MBG trajectory may be more beneficial to assess the potential risk of POD than the blood glucose level at the ICU admission in DM patients undergoing CABG.